2018
DOI: 10.1001/jamapsychiatry.2018.2556
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Foster Care Intervention on Trajectories of General and Specific Psychopathology Among Children With Histories of Institutional Rearing

Abstract: IMPORTANCE It is unclear whether early institutional rearing is associated with more problematic trajectories of psychopathology from childhood to adolescence and whether assignment to foster care mitigates this risk. OBJECTIVES To examine trajectories of latent psychopathology factors-general (P), internalizing (INT), and externalizing (EXT)-among children reared in institutions and to evaluate whether randomization to foster care is associated with reductions in psychopathology from middle childhood through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 44 publications
10
62
0
2
Order By: Relevance
“…This suggests that the foster care children may be more responsive to the higher quality care they receive, and this higher quality care may be protective against later stressful life events. In turn, this may help to explain the lower levels of externalizing problems observed between these groups at age 16 5 . Future studies can help to determine whether the putative buffering effect of higher caregiving quality operates through its influence on stress system development and emerging self-regulatory abilities in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This suggests that the foster care children may be more responsive to the higher quality care they receive, and this higher quality care may be protective against later stressful life events. In turn, this may help to explain the lower levels of externalizing problems observed between these groups at age 16 5 . Future studies can help to determine whether the putative buffering effect of higher caregiving quality operates through its influence on stress system development and emerging self-regulatory abilities in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 96%
“…This is especially important in the context of institutional rearing, as externalizing problems appear more responsive to foster care intervention following institutional care than internalizing problems 2 . Also, after controlling for overlap with other domains of psychopathology, externalizing problems decline over the transition to adolescence among children in foster care, while those with prolonged institutional deprivation show persistent difficulties over this period 5 . This same pattern is not observed for internalizing problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the present study applied a bifactor model that allows for a transdiagnostic quantitative approach to distinguish between different second-order dimensions of psychopathology. While there are methodological limitations when using fit statistics to adjudicate between bifactor and traditional correlated factor models of psychopathology, increasing data indicate the ability of this approach to differentiate meaningful nonspecific and dimension-specific correlates of psychopathology including etiological, concurrent and predictive correlates (Caspi and Moffitt, 2018; Lahey et al, 2017b; Wade et al, 2018). Importantly, in the present study, we identified both broad nonspecific (FA in the body of the CC) and second-order externalizing or internalizing level dimensions (AD in the fornix, sagittal stratum, anterior corona radiata, and splenium of the CC) white matter correlates of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the present study applied a bifactor model that allows for a transdiagnostic quantitative approach to distinguish between different second-order dimensions of psychopathology. While there are methodological limitations when using fit statistics to adjudicate between bifactor and traditional correlated factor models of psychopathology, increasing data indicate the ability of this approach to differentiate meaningful nonspecific and dimension-specific correlates of psychopathology including etiological, concurrent and predictive correlates Lahey et al, 2017a;Wade et al, 2018). Importantly, in the present study, we identified both nonspecific (FA in the body of the CC) and specific (AD in the fornix, sagittal stratum, anterior corona radiata, and splenium of the CC) white matter correlates of psychopathology.…”
Section: Limitations and Conclusionmentioning
confidence: 99%